Mammalian prion amyloid formation in bacteria. Issue 2 (3rd March 2016) - Macedo, Bruno; Cordeiro, Yraima; Ventura, Salvador
ABSTRACT: Mammalian prion proteins (PrPs) that cause transmissible spongiform encephalopathies are misfolded conformations of the host cellular PrP. The misfolded form, the scrapie PrP (PrP Sc ), can aggregate into amyloid fibrils that progressively accumulate in the brain, evolving to a pathological phenotype. A particular characteristic of PrP Sc is to be found as different strains, related to the diversity of conformational states it can adopt. Prion strains are responsible for the multiple phenotypes observed in prion diseases, presenting different incubation times and diverse deposition profiles in the brain. PrP biochemical properties are also strain-dependent, such as different digestion pattern after proteolysis and different stability. Although they have long been studied, strain formation is still a major unsolved issue in prion biology. The recreation of strain-specific conformational features is of fundamental importance to study this unique pathogenic phenomenon. In our recent paper, we described that murine PrP, when expressed in bacteria, forms amyloid inclusion bodies that possess different strain-like characteristics, depending on the PrP construct. Here, we present an extra-view of these data and propose that bacteria might become a successful model to generate preparative amounts of prion strain-specific assemblies for high-resolution structural analysis as well as for addressing the determinants of infectivity and transmissibility.